P116 Assessing the sexual violence services currently provided in genitourinary medicine clinics. (23rd May 2012) - Emerson, C R; Sacks, R; Foster, G E
Abstract : Background: Many patients present to Genitourinary medicine (GUM) clinics following sexual violence (SV) occurring in circumstances including sexual assault (SA), domestic violence (DV), sex work (SW) and trafficking. BASHH has guidelines for SA but not for addressing SV in other situations. Are GUM clinics providing services for these needs? Aims: To assess services currently available in GUM for those disclosing SV. Methods: A cross sectional anonymous online survey of UK GUM clinics was performed. The survey was designed by the authors and piloted. Information was gathered on specific clinics for SV, how often they occur and which members of the multidisciplinary team are involved, and training available for SV. Links with other support services was ascertained. The data were analysed using Microsoft Excel. Results: The response rate was 66/178 (37%), with all regions and deaneries being represented. All responding clinics provide PEP, emergency contraception, STI screen, hepatitis prophylaxis and advice for those presenting after SA. 24% of clinics never use chain of evidence procedures. 80% have a local sexual assault referral centre (of these 87% were happy with this service). 80%, 77%, 50% and 38% have no dedicated clinic for female genital mutilation, sexual trafficking, DV and SW respectively and less than 50% have local training or procedures for these facets. 32% ask about non-consensual sex in all GUM consults, 53% ask this in special groups only. 47% routinely ask about SW. Discussion: There is a wide variation in the SV services available at GUM clinics. Sexual assault services meet guideline recommendations for GUM but SV occurring in other contexts may not be addressed. Sexual violence is increasingly reported and GUM clinics may be the first or only location of presentation. We recommend further training and guidelines to ensure clinics are equipped to meet this need.